Introduction - Verena Balz (A+BE: Architecture and the Built Environment)
Since the 1980s, planning approaches in European regions shifted as a result of increasing attention to spatial patterns of interaction and movement on regional levels of scale, and alongside “a relative decline of the role of the state, a growing involvement of nongovernmental actors in a range of state functions, the emergence of new forms of multi-agency partnerships and more flexible forms of networking at various spatial scales” (Davoudi, 2008, p.63). Upcoming approaches, often called spatial planning, moved attention from the planning of predefined, contained territories to the planning of spatial networks, stretching across multiple and multi-scalar administrative boundaries. Planning that relied on generally applicable rationalities, statutory planning frameworks and authoritative planning power was challenged by planning that relied on an understanding of the specificities of regions, political consent on their desirable futures and the dedication of actors to these visions (Albrechts et al., 2003, Allmendinger and Haughton, 2010, Healey, 2006, Nadin, 2007, Needham, 1988, Schön, 2005). New approaches typically involved coalitions of plan actors from multiple tiers and levels of government as well as market and civil actors. Packaging their interests in shared visions became a way to operationalise planning. Collaboration in decision-making was used to simultaneously legitimise it. In an "institutional void" (Hajer, 2003, p.175) - in near absence of generally accepted and formally approved regional planning guidance - the inclusion of many in decision-making - good governance - became a normative goal of planning in itself (Innes and Booher, 2003, Mayntz, 2004).